Sistem Perawatan Water Treatment Plant (WTP) PLTU Nii Tanasa 3 x 10 MW - La Ode Ahmad Barata (Program Pendidikan Vokasi Teknik Mesin, 2024)
The power plant (PLTU Nii Tanasa) is located in Nii Tanasa Village, Soropia District, Konawe Regency, Kendari - Southeast Sulawesi. This 17.64 ha PLTU consists of 2 units, each producing 10 MW of electricity. The steam power plant system requires a water treatment system to change the water content from sea water to demin water or fresh water (WTP). Water treatment systems in the steam power plants are important to ensure efficient and sustainable operation. The water used in the steam cycle must be of high quality to prevent damage to boilers, turbines, and other components. The stages of water treatment include: Pretreatment, Demineralization, Degasification, Chemical Dosing, blowdown, condensate polishing, cooling water treatment. In the Water Treatment Plant process, the water conductivity is reduced to < 1 μs, this is done so that the electrical conductivity contained in the water is very small so as to minimize the potential for corrosion, and other oxidation processes. In addition to pH, the other parameters of boiler fill water are TDS, and water pH. The types of maintenance observed in this activity are preventive maintenance, and corrective maintenance. Preventive maintenance includes Sea water pump components, multimedia filters, active carbon filters, micron filters, HP pumps, SWRO. The corrective maintainaice in this observation includes micron filter equipment, SWRO, BWRO. The component maintenance process of the WTP has a direct effect on water quality so that it is related to the performance of the Pwer plant for both in terms of thermal performance and economical aspects.